NEMO-Binding Domain Peptide Attenuates Lipopolysaccharide-Induced Acute Lung Injury by Inhibiting the NF-κB Signaling Pathway - Jianhua Huang; Li Li; Weifeng Yuan; Linxin Zheng; Zhenhui Guo; Wenjie Huang (Mediators of Inflammation)
The aim of the present study is to investigate the protective effects and relevant mechanisms exerted by NEMO-binding domain peptide (NBD) against lipopolysaccharide- (LPS-) induced acute lung injury (ALI) in mice. The ALI model was induced by intratracheally administered atomized LPS (5 mg/kg) to BABL/c mice. Half an hour before LPS administration, we treated the mice with increasing concentrations of intratracheally administered NBD or saline aerosol. Two hours after LPS administration, each group of mice was sacrificed. We observed that NBD pretreatment significantly attenuated LPS-induced lung histopathological injury in a dose-dependent manner. Western blotting established that NBD pretreatment obviously attenuated LPS-induced IκB-α and NF-κBp65 activation and NOX1, NOX2, and NOX4 overexpression. Furthermore, NBD pretreatment increased SOD and T-AOC activity and decreased MDA levels in lung tissue. In addition, NBD also inhibited TNF-α and IL-1β secretion in BALF after LPS challenge. In conclusion, NBD protects against LPS-induced ALI in mice.